Noise Complaints and Land Rezoning as a Predictor of Hate Crimes in a New York City Borough - Lettieri, Jess (Journal of interpersonal violence, 2023)
Hate crimes generally have severe victim outcomes compared to other crimes, and therefore warrant further investigation. These types of crimes can often happen in neighborhoods where people from various cultures, socioeconomic backgrounds, religions, etc. meet. Understanding how neighborhood tensions impact the level of hate crimes is important in reducing hate crimes and building community. The current study investigates neighborhood level predictors of hate crimes in a borough of New York City (NYC). Using symbolic threat and defended neighborhoods frameworks, we consider how 311 noise complaints and land use rezoning data can be predictors of hate crimes. We use data from the New York City Police Department (NYPD) and NYC Land Use Tax Output. We find that hate crimes are more likely in the neighborhoods where the noise complaints and land use rezoning are higher than the median. The theoretical implications of these findings are discussed below.